TEACHERS' AND STUDENTS' PERSPECTIVES ON USING DIGITAL EDUCATIONAL TOOLS DURING THE PROCESS OF LEARNING - Grendi Hendrastomo; Nur Endah Januarti (SocioEdu: Sociological Education, 2025)
This research aims to understand how the sociology learning process using digital learning media in high schools in Yogyakarta City. The article presents the proportion and variety of digital learning media used by teachers and students in sociology education. Data were collected using a quantitative approach. The data collection technique used was a questionnaire distributed to students, with data collected from 137 students in 3 high schools. The research results show that the sociology teaching process conducted by the teacher in the classroom combines the use of technology-based learning media. 94.9% of students stated that the teacher allowed the use of electronic devices in the learning process. As many as 98.5% of students stated that they use electronic devices to support the learning process. Various integrations of digital learning media in education, such as the use of laptops, smartphones, and the utilization of the internet to support and enrich learning materials. This is supported by 97.8% of students owning and using laptops, smartphones, and internet access, with a proportion of 0.7% bringing only laptops, 64.2% owning mobile phones, 0.7% bringing both mobile phones and tablets, and 31.4% bringing both laptops and mobile phones to school. Supporting materials are obtained from e-books, YouTube, and articles. The level of media usage by students is 76.6% using e-books, 69.3% accessing YouTube, 10.9% accessing articles, and 66.4% of students using media to understand the material through practice questions.